2010
DOI: 10.1111/j.1365-3040.2010.02122.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐particle‐induced X‐ray emission mapping of elemental distribution in roots of a Mediterranean‐type sclerophyll, Agathosma betulina (Berg.) Pillans, colonized by Cryptococcus laurentii

Abstract: The role of rhizosphere yeasts as plant nutrient-scavenging microsymbionts in resource-limited Mediterranean-type heathlands is unknown. This study, therefore, focused on quantitative elemental distribution within the roots of a medicinal sclerophyll, Agathosma betulina (Berg.) Pillans, grown under nutrient-poor conditions, and colonized by Cryptococcus laurentii. Micro-particle-induced X-ray emission (PIXE) was used to assess quantitative elemental distribution within the roots of A. betulina inoculated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…In addition, the high root RGR and increased BGA observed for these plants indicate that C. laurentii CAB 91 stimulated root growth of blue lupin. This concurs with the work of Cloete et al (2009) where it was found that another C. laurentii strain could improve root growth of buchu, which was attributed to the ability of the yeast to act as a nutrient scavenging symbiont of its host (Cloete et al 2010). It was speculated that this yeast increased the plant's P concentration by accumulating short chain inorganic polyphosphates.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In addition, the high root RGR and increased BGA observed for these plants indicate that C. laurentii CAB 91 stimulated root growth of blue lupin. This concurs with the work of Cloete et al (2009) where it was found that another C. laurentii strain could improve root growth of buchu, which was attributed to the ability of the yeast to act as a nutrient scavenging symbiont of its host (Cloete et al 2010). It was speculated that this yeast increased the plant's P concentration by accumulating short chain inorganic polyphosphates.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, it was not surprising that representatives of C. friedmannii and C. laurentii were isolated from the rhizosphere of free-growing blue lupin during this study. Since some C. laurentii strains are able to improve growth of leguminous (Sampedro et al 2004;Boby et al 2008) and non-leguminous (Cloete et al 2009;Cloete et al 2010) plants, it seemed likely that C. laurentii CAB 91 may act as a PGPY of blue lupin. Therefore, this yeast strain was used during experimentation in the present study and assessed for two plant growth promoting traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from inoculation experiments showed an effect of the spore-associated yeasts on the root growth of rice, suggesting potential tripartite interactions with mycorrhizal fungi and plants (Alonso et al 2008). Cloete et al (2010) studied the role of rhizosphere yeasts as plant nutrient-scavenging microsymbionts in roots of a medicinal sclerophyll, Agathosma betulina, grown under nutrient-poor conditions, and colonized by Cryptococcus laurentii. The average concentrations of P, Fe and Mn were significantly higher in roots of yeast-inoculated plants, compared to control plants that received autoclaved yeast.…”
Section: Soil Yeastsmentioning
confidence: 99%